Semen leukocytes and oxidative‐dependent DNA damage of spermatozoa in male partners of subfertile couples with no symptoms of genital tract infection. (6th May 2016) - Micillo, A.; Vassallo, M. R. C.; Cordeschi, G.; D'Andrea, S.; Necozione, S.; Francavilla, F.; Francavilla, S.; Barbonetti, A.
Summary: The influence of seminal leukocytes on generation of oxidative damage to sperm DNA was here investigated on male partners of subfertile couples asymptomatic for a genital tract infection. The study included 111 ejaculates from men attending the Andrology Centre at University of L'Aquila. Semen leukocytes subset included round cells expressing pan‐leukocyte CD45 antigen, monocyte/macrophage lineage antigen CD14, and activated macrophages HLA‐DR antigen. The 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG) expression identified spermatozoa with DNA oxidative adducts while terminal deoxynucleotidyl transferase (TdT)‐mediated fluorescein‐dUTP nick end labeling (TUNEL) assay detected spermatozoa with DNA fragmentation. Flow cytometry and immunocytochemistry was used for determinations. Main outcome measure was the association of semen leukocyte subpopulations with spermatozoa showing oxidative‐related DNA damage and with routine semen parameters. Leukocyte subpopulations were strictly correlated ( p  < 0.0001), but no association was found between the concentration of leukocytes, semen parameters, the percentage of TUNEL‐positive and of 8‐OHdG‐positive spermatozoa. The percentage of 8‐OHdG‐positive spermatozoa was positively correlated with the percentage of TUNEL‐positive spermatozoa ( r  = 0.48; p  < 0.0001) and negatively correlated with sperm concentration ( r  = −0.44; p  < 0.0001). Sperm concentration and the percentage of TUNEL‐positive spermatozoa independently contributed (β = −0.25, p  = 0.008; β = 0.23, p  = 0.05, respectively) to the variation in percentage of 8‐OHdG‐positive spermatozoa after adjusting for age, abstinence time, and smoking. In conclusion, oxidative‐dependent DNA damage in spermatozoa was associated to poor semen quality but not to different leukocyte subpopulations in ejaculates of men asymptomatic for a genital tract infection.